Highly selective and sensitive optical probe for Fe3+ based on a water-soluble squarylium dye. Issue 20 (11th May 2018) - Xu, Zongguang; Jiang, Mengying; Zhang, Chen; Mei, Jinfeng; Li, Zhongyu; Xu, Song; Wang, Liping
Abstract : A highly selective and sensitive water-soluble optical probe based on a squarylium dye, 2, 3, 3-trimethyl-3 H -indolenine-5-sulfonate squaraine (SQ ) has been successfully synthesized. Abstract : A highly selective and sensitive water-soluble optical probe based on a squarylium dye, 2, 3, 3-trimethyl-3 H -indolenine-5-sulfonate squaraine (SQ ) has been successfully synthesized. The as-preparedSQ can efficiently recognize iron(iii ) ions in the presence of competing cations (Na +, Mg 2+, Al 3+, Cr 3+, Zn 2+, K +, Ca 2+, Ba 2+, Pb 2+, Ni 2+, Co 2+, Ag +, Cu 2+, Cd 2+ ) in deionized water. After Fe 3+ was added, the absorbance and fluorescence of theSQ water solution changed, and the color changed from sky blue to pale yellow. The binding constant ( K a ) ofSQ –Fe 3+ was calculated to be about 1.14 × 10 4 M −1 . Correspondingly, the chelating mode ofSQ –Fe 3+ was confirmed by Job's plot, Fourier transform infrared (FT-IR) and 1 H nuclear magnetic resonance ( 1 H NMR). "Naked eye" detection was performed, which indicated the potential application ofSQ for convenient, selective and fast detection of Fe 3+ .